Enhancing Teachers’ Adaptive Performance: The Role of Organizational Culture, Personality, and Job Satisfaction - Karmila, Nita; Sari, Dini Rusfita (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
The transformation of global education demands the adaptability of teachers, but their adaptive readiness gap affects the quality of learning. The urgency of understanding the quantitative factors driving the adaptive performance of teachers is crucial in the midst of curriculum changes and the integration of digital technology, especially in Indonesia. This quantitative research uses a survey design with path analysis. Data from 122 A-accredited high school civil servant teachers in Bogor were collected via a valid and reliable questionnaire. Data analysis was conducted using IBM SPSS Statistics 21, which included tests for normality, homogeneity, and direct and mediated hypothesis testing (Sobel test). It was found that personality and job satisfaction have a direct impact on teachers’ adaptive performance. Organizational culture does not have a direct effect, but it does significantly affect job satisfaction, which in turn mediates its influence on adaptive performance. Job satisfaction also mediates the relationship between personality and adaptive performance. Theoretically, this study enriches the adaptive work behavior model by confirming the mediating role of job satisfaction, addressing the inconsistencies of the literature. The strategic implication is the need for policies to strengthen a work culture that supports satisfaction as a path to adaptive performance.